1994
DOI: 10.1177/002221949402700110
|View full text |Cite
|
Sign up to set email alerts
|

An Eye-Movement Analysis of the Effects of Scotopic Sensitivity Correction on Parsing and Comprehension

Abstract: Does scotopic sensitivity correction enhance parsing and, thus, comprehension? Twenty-two readers with scotopic sensitivity (mean age = 20.3 yrs.; 40.9% male) parsed sentences under scotopic correction and control conditions. Measures included eye-movement indices of parsing and comprehension questions. Although eye movements suggested enhanced parsing, comprehension scores were not significantly improved with correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Nine studies were identified that had features of RCTs; two publications which report on the same trial are counted as a single study . A consistent definition of IS was applied across these studies and the diagnostic procedures involved the use of the Irlen proprietary testing materials delivered by Irlen trained staff.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were identified that had features of RCTs; two publications which report on the same trial are counted as a single study . A consistent definition of IS was applied across these studies and the diagnostic procedures involved the use of the Irlen proprietary testing materials delivered by Irlen trained staff.…”
Section: Resultsmentioning
confidence: 99%
“…There may also be a cyclic effect, with increases in meaning providing greater access to semantic patterns in text as an aid to word identification (Denckla, 1996;Schwantes, 1991;Stanovich, 1986). When this greater access to semantic patterns is combined with reported improvements in span of recognition, it may further enhance the flexibhty of eye movements required for comprehension, as has been found with the use of coloured filters (Fletcher & Martinez, 1994;Holland, et al, 1991;Tyrrell, et al, 1995).…”
Section: Reading Achievementmentioning
confidence: 97%
“…(1987Rosenhall etal. ( , 1996 found abnormal saccades and disturbed smooth pursuit eye movements in large numbers of subjects with CFS, and similar symptoms have been identified in subjects with IS (Fletcher & Martinez, 1994;Tyrrell et al, 1995). Potaznik and Korol (1992) compared subjects with CFS and Immune System Dysfunction to healthy controls, with significant differences in ocular symptoms being identified (p=0.0001 to 0.007).…”
Section: A Preliminary Investigation Of Biochemical Anomaliesmentioning
confidence: 81%